Cobalt nanoparticles incorporated into hollow doped porous carbon capsules as a highly efficient oxygen reduction electrocatalyst. Issue 20 (17th September 2018) - Guo, Feng; Yang, Hui; Aguila, Briana; Al-Enizi, Abdullah M.; Nafady, Ayman; Singh, Mandeep; Bansal, Vipul; Ma, Shengqian
Abstract : MOF nanocrystals are employed for the design and synthesis of cobalt nanoparticles embedded into hollow doped porous carbon electrocatalyst. Abstract : Platinum-based materials have been the dominant and best electrocatalysts for promoting the oxygen reduction reaction (ORR). However, going beyond state-of-the-art catalysts remains a great challenge. Recently, nanostructured composites of conductive carbons and earth-abundant metals have emerged as promising electrocatalysts. Herein, we report a facile and practical approach for the synthesis of cobalt nanoparticles embedded into hollow nitrogen/cobalt-doped porous carbon capsules (Co@NPCC). The fabrication of this material was achieved via the thermal decomposition of sacrificial metal–organic framework nanocrystals coated with a metal–tannic acid coordination polymer shell, upon pyrolysis, which delivers zerovalent cobalt nanoparticles embedded in the walls of hollow capsules. Co@NPCC proved to be a superb catalyst for the electrochemical ORR, showing a highly positive onset potential (∼1.02 V vs. RHE) and current density (∼5.2 mA cm −2 ) in 0.1 M KOH electrolyte. These values are in excellent agreement with those reported for the state-of-the-art Pt/C catalyst. Significantly, materials produced via this approach can be manufactured on a large scale, thereby providing access to next-generation catalysts for important electrochemical processes.